Determinants of Perinatal Death in The Work Area of Sikumana Health Center in Kupang City - Posidius Eriksius Soli Wele; Anna Henny Talahatu; Rina Waty Sirait (Universitas Nusa Cendana, 2022)
Perinatal death is defined as fetal mortality at 28 weeks or more of pregnancy, as well as infant death within the first seven days of life. Pregnant women's nutritional status is one indicator that can be used to assess the risk of perinatal mortality. The goal of this research was to look at the factors determining perinatal death in the Sikumana Health Center Work Area in Kupang City. An analytic survey with a case-control design was used in this study. This study was conducted in the Sikumana Health Center's working region in Kupang City in November - December 2020. The study population was divided into two groups, the case population was mothers with cases of perinatal death totaling 38 people and the control population was mothers who had live births totaling 1,118 people. The sample consisted of 114 people grouped with 1:2 ratio of 38 cases and 76 controls. The sample was selected using simple random sampling. The results showed that there was an effect of hemoglobin level (p-value=0.000) and upper arm circumference (p-value=0.000) with perinatal mortality. Pregnant women need to increase their knowledge about balanced nutrition by accessing information from health media and consulting health workers at the nearest health facility.